The Effectiveness of Counterpressure Massage in Reducing Pain Intensity During the First Stage of Labor Active Phase - Fathiyati, Fathiyati; Octavia, Rina; Handayani, Fitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The process of releasing the fetus known as childbirth is marked by contractions that thin the uterus and cervix, resulting in pain during labor. Every woman who is about to give birth will experience physiological labor pain. Counterpressure massage is one way to ease labor pain. The purpose of this study is to ascertain whether or not counterpressure massage reduces the intensity of pain during labor's active phase. A pre- and post-test, one-group, control design, and a sample size of 60 respondents were used in this study. The Wilcoxon test was used to conduct an analysis and observation sheets were used to collect data. The examination results show that counterpressure knead is viable in decreasing torment force during the main phase of work in the dynamic stage, which is demonstrated by the aftereffects of information examination where the p-esteem = 0.000 < 0.05 so the outcomes got are that H0 is dismissed and H1 is acknowledged. The examination results show that counterpressure knead is viable in lessening torment force during the main phase of work in the dynamic stage, which is demonstrated by the consequences of information investigation where the p-esteem = 0.000 < 0.05 so the outcomes got are that H0 is dismissed and H1 is acknowledged. Counterpressure massage is an effective alternative that should be used to ease labor pain during the first active stage.